2011
DOI: 10.1111/j.1600-0668.2011.00725.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparing mixing and displacement ventilation in classrooms: pupils’ perception and health

Abstract: Both mixing and displacement ventilation may be appropriate in school classrooms as long as the overall design, ventilation rates, and maintenance of systems are satisfactory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 29 publications
0
28
0
Order By: Relevance
“…Second, several IAQ constituents have demonstrated diurnal and seasonal variation, complicating exposure assessment strategies. Third, school IAQ is dependent on multiple construction factors and school location . Further, occupants may be the source of biological pollutants in schools .…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, several IAQ constituents have demonstrated diurnal and seasonal variation, complicating exposure assessment strategies. Third, school IAQ is dependent on multiple construction factors and school location . Further, occupants may be the source of biological pollutants in schools .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Further, occupants may be the source of biological pollutants in schools . Subjective perception of air quality, rather than objective air quality measures, may play a greater role in occupants' health and performance . In terms of the social milieu of the school, school climate has been challenging to define and measure; there is no consensus operationalization or widely accepted standardized tool to assess school climate .…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the 2004 study, none of these variables is reported as significant. Other researchers obtained significant results between CO 2 reduction and the perception of air quality, specifically in connection with the freshness of the air, the perception of lower temperatures, increased perception of air movement and decreased perception of odors [14,[40][41][42][43].…”
Section: Co 2 Effects On the Perception Of Comfortmentioning
confidence: 99%
“…The interest in optimizing DV systems in classrooms and lecture rooms is mainly because of the fact that DV possesses the advantage of low noise, due to having low speed air supply, which is optimal for classroom use 9 . The connection between indoor air quality and students' health and academic performance as proved by multiple studies factors in as well 10,11 . Wachenfeldt et al.…”
Section: Introductionmentioning
confidence: 99%
“…recommended that CO 2 concentration should be kept below 1000 ppm at 1.2 m height 11 . However, it is noticed that school classroom, 8,10,11,12,13 is more widely studied than university lecture halls 14,15 . The reason is believed to be that children are more vulnerable to low indoor air quality 10 …”
Section: Introductionmentioning
confidence: 99%